AYURVEDIC MANAGEMENT OF YUVANPIDIKA WITH ORAL MEDICATION, JALAUKAVCHARANA AND NIDANPARIVARJANA – A CASE REPORT - Dr. Hitesh Dagar ,Dr Sanamika Gupta, Dr Anjali Sharma; Dr Laxmikant S D (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
Yuvanpidika is a type of Kshudra Roga. The diseases which are Kshudra or diminutive in nature, whose symptoms and signs are less in quantity and quality compared to other diseases and which are not life threatening are termed as ‘Kshudra -rogas ’ in Ayurvedic context. Alternative name for Yuvanpidika is Mukhadushika. Acne Vulgaris is its contemporary equivalent. It is the chronic inflammation of sebaceous glands. Modern medicine takes a lot of time and may have side effects on prolonged use along with comparatively fewer long-lasting positive outcomes. The younger generation is well aware of the benefits of holistic approach towards beauty and seeks for appropriate guidance for a healthy lifestyle in addition to treatment. In the current study, an adolescent girl with grade 3 acne vulgaris was treated for one month only with Ayurvedic treatment which comprised of oral medication, Jalaukavacharana and Nidanaparivarjana. She was also counselled afterwards to adopt a healthy lifestyle and appropriate diet was advised to her.